Size-relationship between transverse and arcuate foramina of atlas vertebrae in a modern South African skeletal population sample - Glen J. Paton; Keegan G. Reynolds; Shahed Nalla (Translational Research in Anatomy)
Background: This exploratory quantitative study examined the relationship between the transverse foramen (TF) and the anomalous arcuate foramen (AF) in the atlas vertebrae of a South African skeletal population comprising two cohorts, namely an AF-Present (AF-P) groups (n = 60) and an AF-Absent (AF-A) control group (n = 60). Methods: The study analyzed the size relationship between the AF, and ipsilateral and contralateral TF. Potential correlations between TF dimensions and AF presence were evaluated using metric and non-metric shape assessments. Results: In the AF-P cohort, the mean surface area of the left AF measured 31.46 mm2, and the left TF measured 31.52 mm2. The mean surface area size of the right AF was 30.96 mm2, while the right TF measured 30.24 mm2. The TF mean surface area in the AF-P group was larger than the AF-A group, with mean areas of 2.57 mm2 and 1.78 mm2 larger (left: 28.95 mm2 and right: 28.46 mm2, respectively). Males exhibited significantly larger TFs than females on the right side for anteroposterior, transverse and surface area measurements. The surface area of the right AF correlated strongly with the width and surface area of the left TF, and only the surface area of the right TF. Conclusion: The general trend was that when the right AF surface area increased, as did the dimensions of the TF bilaterally. These findings highlight the clinical relevance of the size-relationship of AF and TF size variations, which may affect vertebral artery dynamics with movements or cervical spine manipulation.